El método Fartlek y la resistencia a la velocidad en futbolistas - Paz Guachilema, Henry Sebastián (2023)
The present investigation called "The Fartlek method and the resistance to speed in soccer players" was to apply a training program based on the Fartlek method as a predominant factor in soccer players of the soccer school Golazo of the parish of San Andres to improve the resistance to speed through training sessions based on the fartlek method which takes into account the age of the athlete, the intensity and duration of the work for a better result. The study is going to be a field study in which we are going to perform Bansgbo sprint test, also bibliographic documentary, exploratory, descriptive and correlational variables. And in case there is any doubt about its effectiveness, it should be borne in mind that the fartlek method will not only allow progress and increase performance in competition, but also brings other benefits such as improved power, endurance and cardiovascular system itself. For the development of this program, a macrocycle of 12 weeks of intervention was used, where the Swedish and Polish Fartlek method was prioritized in the training sessions, considering the individual physical condition of the soccer players, the appropriate intensities were applied to each one of them. The main results showed an improvement in the resistance to intense work and a lower fatigue index of the soccer player when changing direction.